A Theology of Southeast Asia: LiberationPostcolonial Ethics in the Philippines - Isherwood, Lisa (Asian Horizons, 2019)
Agnes M. Brazal, A Theology of Southeast Asia, LiberationPostcolonial Ethics in the Philippines, Maryknoll, New York: Orbis Books, 2019. Pages: 204. ISBN 978-1-62698-292-5.